Alone We Are Rare, Together We Are Strong: A Review of the National Organization for Rare Disorders (NORD®). Issue 4 (2nd October 2022) - Phillips, Kat
Abstract: The National Organization for Rare Disorders, or NORD ®, is a robust resource suitable for patients, families, clinicians, researchers, and advocates of those living with or impacted by rare diseases. Given that rare diseases affect around 30 million people in the United States, half of which are estimated to be children, it is vital to have access to credible and accessible information. An added bonus of NORD is their staunch advocacy platform, which brings to light other consumer health information which may otherwise be hard to find. This consumer health resource review covers the consumer-focused aspects of NORD.